2012
DOI: 10.2215/cjn.10251011
|View full text |Cite|
|
Sign up to set email alerts
|

Serum Albumin as Predictor of Nutritional Status in Patients with ESRD

Abstract: SummaryBackground and objectives Serum albumin is a widely used biomarker of nutritional status in patients with CKD; however, its usefulness is debated. This study investigated serum albumin and its correlation with several markers of nutritional status in incident and prevalent dialysis patients.Design, setting, participants, & measurements In a cross-sectional study, serum albumin (bromocresol purple), and other biochemical (serum creatinine), clinical (subjective global assessment [SGA]), anthropometric (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
103
2
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(115 citation statements)
references
References 29 publications
3
103
2
7
Order By: Relevance
“…Although serum albumin is still considered a biomarker of nutritional status in dialysis patients, it correlates poorly with nutritional status markers in this patient group. 48,49 Several groups have reported that the strong association between serum albumin and mortality in dialysis patients is explained by persistent inflammation rather than by malnutrition. 49,50 Finally, BMI is a crude marker of body composition and does not accurately differentiate between lean and fat tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Although serum albumin is still considered a biomarker of nutritional status in dialysis patients, it correlates poorly with nutritional status markers in this patient group. 48,49 Several groups have reported that the strong association between serum albumin and mortality in dialysis patients is explained by persistent inflammation rather than by malnutrition. 49,50 Finally, BMI is a crude marker of body composition and does not accurately differentiate between lean and fat tissue.…”
Section: Discussionmentioning
confidence: 99%
“…plasma volume) and urinary albumin losses. 17 Moreover there is a reduction in the albumin synthesis during acute illness. The presence of acute or chronic inflammation limits the specificity of serum albumin as a nutritional marker.…”
Section: Discussionmentioning
confidence: 99%
“…Bu sebeple serum albümin seviyesinin diyaliz hastalarında beslenme durumunu belirlemek için iyi bir belirleyici olmadığı öne sürülmektedir (12,16). Tüm bu sonuçlara ve beslenme durumunu saptamak için kullanılabilecek farklı alternatif metotlara rağmen kronik böbrek yetmezliği olan hastalarda beslenme durumunun saptanmasında en yaygın olarak serum albümin seviyesi kullanılmaktadır (17). Serum albümin düzeyi 4.0 g/dL'nin altında olan hastalar malnütrisyonlu olarak tanımlanmaktadır (15).…”
Section: Malnütrisyon Göstergesi Olarak Hipoalbüminemiunclassified
“…Üremi ve üremik sendroma eşlik eden semptomlar proinflamatuvar sitokinlerin aktivasyonuna neden olmakta ve bu hastalarda normal popülasyona göre serum proinflamatuvar sitokinlerinin 10 kat daha yüksek olduğu bilinmektedir (1,14). Ayrıca, SDBY olan hastalarda akut faz birlikte görülmesi ise serum albümin seviyesinde oldukça büyük bir düşmeye neden olmaktadır (16,17). Bunun yanında HD ve PD esnasında görülen ekzojen kayıplar da hipoalbüminemiye yol açmaktadır.…”
Section: İnflamasyonunclassified